Youth voice in Nigerian school-based management committees - Umar, Bashiru Bako; Krauss, Steven Eric; Abu Samah, Asnarulkhadi; Abdul Hamid, Jamaliah (Australian International Academic Centre, 2017)
In Nigeria, School-Based Management Committees (SBMCs) aim to provide an opportunity for all stakeholders, particularly the vulnerable groups in the school’s host communities such as young people and women to partake in school governance. Research on the experiences of youth voice in the committees is scant, however, as much of the existing literature on SBMCs focuses on program outcomes. Using qualitative research interviews, observations, and document analysis, this study addressed this gap by exploring how youth participate and express themselves in two SBMCs in Niger State, Nigeria. The findings, which were derived from 19 youth and adult participants, were drawn from SBMC members out of which 12 were youth between the ages 13 and 25, while 7 were adults aged 40 and above. The participants revealed that youth committee members expressed their voice in the committees through participating in a number of committee activities. Specifically, the youth participated in decision-making during meetings, aided in the construction of committee projects, undertook administrative/managerial functions and monitored the committee’s projects. They also participated in revenue generation, planning, school visits and supervision, advocacy, and sensitization campaigns.